A Proposal for Sustainability of a Palimpsest City: Nicaea - Kırlı Özer, Gözde; Çahantimur, Arzu (ICONARCH International Congress of Architecture and Planning, 2017)
Turkey is a geography situated on important commerce roads like Spice Road & Silk Road connecting Asia and Europe. With the advantage of its location, Turkey has a mild climate and rich soil. Because of this physical and geographical characteristics Turkey hosted different civilizations throughout history. All civilizations located in Turkey made their own settlements and some parts of this settlements ruined because of various reasons like wars, natural disasters, migrations etc. and became layers buried underground. This layers gradually increased during history and turned Anatolia lands into a palimpsest structure. Although not having the same significance for Ottoman Empire, Nicaea has been the capital city of Byzantium Empire. For its religious and military importance, council meetings held in the city. Thus, many important historic buildings. Because of these specialties the city was accepted to UNESCO temporary heritage list in 2015. In our days many researches and excavation works are in progress to determine and reveal the historic and cultural layers of the city. In the scope of this research; Nicaea as being one of the most valuable cities of Turkey and Anatolian history, will be examined in comparison with Thessaloniki (Greece) ve Byblos (Lebannon, Jbail) cities for their similar palimpsest structures and historical importance. Research will be done by literature review and map analysis on cities functional structures. The aim of this research is to compare these three palimpsest cities by means of their physical, social and spatial properties. The findings will be used to propose strategies in order to achieve cultural and historical sustainability of Nicaea.